Linguistic Landscape Study of Culinary Signage on Palagan Street, Yogyakarta (e-Journal of Linguistics, 2025)
Yogyakarta is a multilingual centre with educational institutions, residential areas, workplaces, culinary establishments, and many more. Palagan Street is one of the busiest areas with various linguistic elements, especially on culinary signage. This study aims to examine the types of language patterns found on culinary signs that signify linguistic diversity and to describe the linguistic strategies used in the signage. The observation technique was conducted by photographing 69 signage on Palagan Street, which showed that most of the signs used Indonesian. A descriptive qualitative method was applied to analyze the linguistic strategies used. The findings show the dominance of bilingual signs (49%) in Indonesian-English, followed by monolingual signs (44%) in Indonesian, and multilingual signs (7%), which include Indonesian-Japanese-English. The linguistic strategies identified include code-mixing, symbols, speech acts, abbreviations, figurative language, lexical blends, schemes, and politeness strategies. This research contributes theoretically by providing insights into language use and strategies in culinary signage in the linguistic landscape of Yogyakarta and practically by providing information on design considerations for multicultural public spaces.
Keywords: Linguistic Landscapes; Multilingualism; Cultural Identity; Linguistic Strategies; Language Diversity